2003
DOI: 10.1073/pnas.2336092100
|View full text |Cite
|
Sign up to set email alerts
|

Target-specific utilization of transcriptional regulatory surfaces by the glucocorticoid receptor

Abstract: The glucocorticoid receptor (GR) activates or represses transcription depending on the sequence and architecture of the glucocorticoid response elements in target genes and the availability and activity of interacting cofactors. Numerous GR cofactors have been identified, but they alone are insufficient to dictate the specificity of GR action. Furthermore, the role of different functional surfaces on the receptor itself in regulating its targets is unclear, due in part to the paucity of known target genes. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
200
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(216 citation statements)
references
References 58 publications
14
200
1
1
Order By: Relevance
“…However, the GME appears to be equally active with both endogenous and synthetic reporter genes Szapary et al, 1992;Collier et al, 1996). Furthermore, it is clear from microarray studies that endogenous genes yield a spectrum of responses that resist generalization (Mittelstadt and Ashwell, 2003;Rogatsky et al, 2003;Donn et al, 2007;Kininis et al, 2007). Therefore, the present results establish that various factors can unequally alter the transcription properties of PR vs. GR in a model system that most likely is recapitulated by some endogenous regulated genes.…”
Section: Discussionmentioning
confidence: 50%
“…However, the GME appears to be equally active with both endogenous and synthetic reporter genes Szapary et al, 1992;Collier et al, 1996). Furthermore, it is clear from microarray studies that endogenous genes yield a spectrum of responses that resist generalization (Mittelstadt and Ashwell, 2003;Rogatsky et al, 2003;Donn et al, 2007;Kininis et al, 2007). Therefore, the present results establish that various factors can unequally alter the transcription properties of PR vs. GR in a model system that most likely is recapitulated by some endogenous regulated genes.…”
Section: Discussionmentioning
confidence: 50%
“…In general, we were struck by the remarkable degree of cell and gene specificity inherent in androgen regulation, as 182 (89%) of the 205 ARGs we identified were apparently androgen-unresponsive in LNCaP cells (DePrimo et al 2002;Nelson et al 2002). Similarly, comparisons of glucocorticoid-responsive genes in different cell types (Rogatsky et al 2003;Wang et al 2004;Phuc Le et al 2005;So et al 2007) revealed little overlap. It will be important in future work to assemble expression and response data from multiple androgen-responsive cell types to better define and understand tissue-specific transcriptional networks radiating outward from AR.…”
Section: Figure 6 Distribution Analysis Of Ares Located Near Args (A)mentioning
confidence: 94%
“…We interrogated ∼104 kb genomic regions centered on the transcription start sites of 548 candidate hormone-responsive genes to identify AREs and to determine the distribution of AREs at promoter proximal, distal, and intragenic regions. These human candidate genes included our 157 putative and validated ARGs identified in HPr-1AR cells, 241 putative and validated glucocorticoid receptor-(GR) responsive genes identified in A549 lung adenocarcinoma cells and U2OS-GR osteosarcoma cells (Rogatsky et al 2003;Wang et al 2004;So et al 2007), and 150 genes potentially hormone-responsive in other cell types (e.g., 35 ARGs from LNCaP cells; DePrimo et al 2002;Nelson et al 2002). GR, which is closely related to AR, binds in vitro with similar affinity as AR to consensus sequences in the elementary halfsites GGTACAnnnTGTTCT (Claessens et al 2001).…”
Section: Identification Of Ar Binding Regionsmentioning
confidence: 99%
“…In transfected cells the induction of GILZ by GC was dependent on dimerization of GR (Rogatsky et al, 2003), although GILZ expression in the GR dim A c c e p t e d M a n u s c r i p t…”
Section: A Clarkmentioning
confidence: 99%
“…In transfected cells GR dim is capable of inducing at least some GC target genes (Rogatsky et al, 2003), cooperative gene regulation by GCs and STAT5 is spared in the GR dim mouse (Tronche et al, 2004), and at least one antiinflammatory mediator is effectively induced by GCs in murine macrophages expressing only GR dim (Abraham et al, 2006). In the absence of microarray data describing global transcriptional changes in cells expressing GR dim , it is too early to conclude how broadly and how strongly the induction of gene expression by GCs is impaired, therefore it remains a strong possibility that this mutation does not A c c e p t e d M a n u s c r i p t…”
Section: Evidence In Favour Of Transrepressionmentioning
confidence: 99%